1992
DOI: 10.1289/ehp.9297225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactant components and exposure geometry on the effects of quartz and asbestos on alveolar macrophages.

Abstract: Bovine (BAM) and rat (RAM) alveolar macrophages were incubated in vitro with DQ12 quartz or UICC chrysotile asbestos either alone or in the presence ofdipalmitoyl lecithin (DPL). The reaction of the cells of both species to the untreated dust particles w similar quaHtatively and quantitatively, withalos ofviabibt and releaseof lacate and N-acetyl-3l-glucosaminidase after 20 hr ofincubation. In the presence ofDPL, the toxicity ofquartz to BAM disappeared completely, whereas the protective influence of the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
19
0
3
Order By: Relevance
“…Gülden and Seibert (2005) have recently reported that the bioavailability of chemicals in vitro can be reduced due to partitioning into lipids and binding to serum proteins. The 'protective' eVect of serum in silica toxicity has also been well documented (Emerson and Davis, 1983;Schimmelpfeng et al, 1992). demonstrated that coating of silica with a commercially available bovine pulmonary surfactant aVorded short-term protection against its toxicity when tested both in vitro on rat alveolar macrophages and in vivo following intratracheal instillation.…”
Section: Discussionmentioning
confidence: 93%
“…Gülden and Seibert (2005) have recently reported that the bioavailability of chemicals in vitro can be reduced due to partitioning into lipids and binding to serum proteins. The 'protective' eVect of serum in silica toxicity has also been well documented (Emerson and Davis, 1983;Schimmelpfeng et al, 1992). demonstrated that coating of silica with a commercially available bovine pulmonary surfactant aVorded short-term protection against its toxicity when tested both in vitro on rat alveolar macrophages and in vivo following intratracheal instillation.…”
Section: Discussionmentioning
confidence: 93%
“…The same research group used amiodarone to inhibit phospholipase activity and generate phospholipidosis artificially, which proved to be protective with silica exposure, again having no effect on PMN influx [27]. The surfactant PL component dipalmitoyl phosphatidylcholine (DPPC, also referred to as dipalmitoyl lecithin) has been used as a protective pre-coating agent against silica toxicity [28][29][30], but was ineffective at inhibiting chysotile asbestos toxicity [29]. In addition, SPA and D have been used to attenuate silica toxicity in vitro [19,20].…”
Section: Modification Of Silica Toxicity By Lung Surfactantmentioning
confidence: 99%
“…In view of the potential discrepancies, a few groups have begun to evaluate the effects of serum on particle toxicity from the aspect of particle agglomeration and surface chemistry (Davoren et al 2007; Murdock et al 2008; Zhu et al 2009). For example, the presence of protein-containing serum in a medium has a protective effect on the toxicity of both silica and single-walled carbon nanotubes (Schimmelpfeng et al 1992; Davoren et al 2007). Recently, studies have found that the protective effect on NP toxicity was derived from the binding of multiple layers of serum proteins (e.g., bovine fibrinogenon, gamma globulin, etc.)…”
Section: Introductionmentioning
confidence: 99%